PROSES KOMUNIKASI KEBIJAKAN PARIWISATA PADA DISBUDPAR PROVINSI JAWA TIMUR - Anggara Putra Harastinanda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
After the Covid-19 Pandemic in 2022 the tourism sector has reopened so that it requires an active role from government agencies to restore the tourism sector. One of these government agencies is DISBUDPAR East Java Province. To carry out its policies, of course, organizational communication is needed. To see how the internal communication of the East Java Province DISBUDPAR organization runs, research is needed to see the tourism policy communication process. The purpose of this study is to determine the internal organizational communication process related to tourism policy at DISBUDPAR of East Java Province and see the similarities and differences in the period before and after the Covid-19 pandemic (2019-2022). This research uses organizational communication theory that focuses on internal institutions and government communication that focuses on staff management. The type of research is qualitative with a case study approach. Data collection methods are interviews with four employees of DISBUDPAR East Java Province, observation and documentation. The results of the study are communication in DISBUDPAR East Java Province is still dominated by one-way communication, namely orders from leaders to their members. During the period before to after the Covid-19 pandemic (2019-2022) there were several changes in the DISBUDPAR of East Java Province related to tourism policy communication. From this research, it can be seen how the organizational communication process within the internal DISBUDPAR of East Java Province and what has changed and remains consistent in the communication process during the period before to after the Covid-19 pandemic (2019-2022).